Inside the virtual classroom: Student perspectives on affordances and limitations - Garry Falloon (Flexible Learning Association of New Zealand, 2012)
Research indicates learners studying at a distance can traditionally experience perceptions of isolation and lack of 'belonging' and support, which can adversely affect their learning experience and performance (McInnerney & Roberts, 2004; Moore, 1997; Picciano, 2002). Recently, the advent of Web2-based technologies combined with increasingly affordable, accessible and reliable broadband, has meant that a whole new array of digital tools have become viable to support synchronous interaction between students and tutors engaged in online learning, thereby potentially helping to address some of these issues. This paper presents findings from a study involving postgraduate students using the Adobe Connect and Wimba virtual classrooms, to present a series of seminars as part of Waikato University's postgraduate diploma in Education. It explores students' perspectives of the value of the classrooms for supporting communication and interaction, and examines factors that influenced the quality of their experience. Results show that while virtual classroom use was viewed favourably, their value was influenced by task, tool, media and technical factors - some of which were beyond student control. These factors will be explored and discussed, with recommendations being presented for teachers considering using synchronous virtual classrooms to support their online distance offerings.